Ecclesiastical Economies: The Integration of Sacred and Maritime Topographies of Late Antique Cyprus - Catherine T. Keane (MDPI AG, 2021)
This article focusses on the relationship of the church with productive landscapes and coastal topographies within numerous Cypriot contexts of the 4th–8th centuries. Through synthesising the archaeological research and architectural remains of these aspects and categories, the coastal settlements of the island are recontextualised in terms of their mercantile, religious, and cultural networks, on inter- and intraregional scales. The advantages of researching late antique insular societies on local, individual scales and within economic contexts are therefore highlighted. These integrative approaches can illuminate the constructions of religious identity across many coastal contexts, particularly in larger islands with micro-regions and trans-Mediterranean connectivity, like Cyprus. By considering the importance of the administrative and economic roles of the late antique church within these maritime topographies, future archaeological research can integrate both the monumentality and pragmatic aspects of sacred landscapes.